Side effects of Sinopharm Vaccine experienced by healthcare professionals of Holy Family Hospital, Rawalpindi, Pakistan - Rizwana Shahid , Muhammad Umar , Muhammad Mujeeb Khan , Shazia Zeb , Ayesha Nadar ,Sheema Afzal (Journal of Rawalpindi Medical College, 2021)
Objectives: To determine the gender and age based disparities in side effects among healthcare workers in response to COVID-19 (Sinopharm) vaccination Subjects & Methods: Total 216 healthcare workers were vaccinated against COVID-19 by administering Sinopharm vaccine during February and March 2021 at Infectious Diseases Department of Holy Family Hospital Rawalpindi were enrolled in the study through consecutive sampling. Data for this cross-sectional descriptive study was gathered pertinent to age, gender and side effects of Sinopharm vaccination. The information regarding vaccination side effects was inquired through telephonic calls. Data was analyzed by means of SPSS version 25.0. Results: Mean age of healthcare workers in our study was 35.7 ± 9.5 years. Most (54.6%) of them were females. About 79.2% of health professionals were 21-40 years old. Side effects after first dose of Sinopharm vaccine were experienced by 46.3% males and 42.4% females. About 45.2% and 42.3% males and females respectively overlooked the second jab adversity. Greater proportion (43.6%) complained of vaccine related side effects after the second dose than 37.5% subjects who noted side effects after the first dose of vaccine. Bodyaches, injection site pain, headache and fever were established as the commonest post-vaccination side effects. Conclusion: Side effects resulting from Sinopharm vaccine among our healthcare personnel were minimal. Fortunately none of them complained of serious aftereffects. Despite the COVID vaccination, our healthcare workers should strictly adhere to COVID SOPs amidst pandemic in order to avoid catastrophe in future.